Recent progress in camel research - Ashraf M. Abu-Seida; Marwa H. Hassan; Abdulrahman Abdulkarim; Elham A. Hassan (Open Veterinary Journal)
Background: Camelids play an important role in the preservation of ecosystems, biodiversity, food security, economic growth, adaptation to climate change, and cultural and social aspects. Therefore, the United Nations (UN) has named 2024 the International Year of Camelids (IYC).